Histological study of the thyroid tissue in carp fish (Cyprinus Carpio) in Summer and Winter: Amer M Hussin and Yahia Yass Khudher - Khudher, Yahia Yass (The Iraqi Journal of Veterinary Medicine, 2016)
This study is designed to investigate the effect of temperature on thyroid gland of 24 adult healthy female carp fish (12/ season). Neutral buffered formalin solution10% was used for fixation and routine histological techniques. Hemotoxline and Eosine and PAS stains were, also used. The results revealed that the thyroid tissue in carp fish was closely associated with the renal and sub pharyngeal tissue. Spleen and liver did not show any thyroid follicles. The thyroid tissue of carp fish consisted of disseminate thyroid follicles not surrounded by apparent capsule. Different sizes and shapes of thyroid follicles were observed. The follicular cells form tight epithelium. Para follicular cells were distributed among the follicles. The seasonal thyroid follicles were often filled with colloid summer and winter. In conclusion the study was classified glands units of the thyroid tissue into two states: The first stat of the low activity in winter its cells were epithelial flat to squamous and follicles almost filled with homogeneous, while the state of activity in the Summer, follicular homogenous colloid cells were cuboidal follicular and sessile to high contain homogeneous diluted colloid.